Profil Penggunaan Antibiotik Pada Pasien Infeksi Saluran Pernapasan Akut (ISPA) Balita di Beberapa Pelayanan Kesehatan - Salsabilla, Kharisma; Nurmasuri, Nurmasuri; Wardhana, Muhammad Fitra (CV. Jasa Sukses Abadi, 2024)
Acute Respiratory Infection (ARI) is a disease caused by the transmission of pathogens that infect the respiratory tract and result in disruption of normal respiratory activities in individuals. The cause of ARI itself can come from a viral or bacterial infection. Therapy for ARI caused by bacteria can use antibiotics. Giving antibiotics for ARI depends on the bacteria causing it. The principles of using antibiotic therapy are empirical therapy and definitive therapy. This literature study aims to determine the percentage of antibiotic use and the choice of antibiotics most frequently given to ARI patients. This research uses a literature review method with a search for articles using Google Scholar, Science Direct and Pubmed published in 2018-2024. Journals are collected using journal websites from searches using relevant keywords. After that, they are assessed regarding eligibility according to relevant researchers' criteria and a relevant review is carried out. The results of the review show that the use of antibiotics as ARI therapy often occurs, the use of antibiotics being the most frequently used in ARI such as amoxicillin and cephalosporin which have the same function and effectiveness. Antibiotics for clinical symptoms should be given based on clear indications, antibiotic administration should be based on the results of microbiological examination. This literature review can be used to evaluate the appropriateness of using antibiotics as an effort to prevent resistance.